Gadolinium aluminum borosilicate fluorine oxygen scintillation glass and preparation method thereof
By using cerium-doped gadolinium aluminoborosilicate composition and specific preparation technology in scintillation glass, the problem of insufficient performance in high-energy physical experiments is solved, and high density, high light yield and fast attenuation time is achieved. It is suitable for nuclear radiation detection and high-energy physical experiments.
Patent Information
- Application Number
- CN202411861252.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-18
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
In high-energy physics experiments, existing scintillation glasses are difficult to take into account the performance requirements of high density, high gloss yield and fast attenuation time, and contain heavy metal oxides, which pollute the environment and cost high.
The cerium-doped gadolinium aluminoborosilicate fluorooxyfluoroglycollimated glass is used to reduce the melting temperature by replacing gadolinium oxide with gadolinium fluoride, combined with a reducing atmosphere or a reducing silicon source preparation process, to achieve both high density and high gloss yield.
The prepared scintillation glass has a density of 6.0g/cm3 or above, and its optical output exceeds 1000ph/MeV, meeting the needs of CEPC hasin energy generators, and has excellent performance in nuclear radiation detection, high-energy physical experiments and other fields.
Smart Images

Figure CN119683852A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of scintillation materials, and in particular to a colorless and transparent gadolinium aluminum borosilicate fluoride-oxygen scintillation glass and a preparation method thereof. Background Art
[0002] Scintillator detectors, as one of the most important radiation detectors, are often used in high-energy physics experiments, nuclear radiation detection, nuclear medicine, and industrial flaw detection. Scintillator materials can convert high-energy particles or rays into visible light and are optical functional materials. Generally, solid scintillator materials can be divided into scintillator crystals, scintillator ceramics, plastic scintillators, and scintillator glass. Scintillator crystals have excellent performance, but their growth process is complex and costly. Plastic scintillators have extremely fast decay time and stable performance, but they have low density and poor radiation resistance. Scintillator ceramics have good physical and chemical stability and good scintillation performance. Due to the large number of pores inside, it is difficult to achieve high transparency and the preparation cost is high. Therefore, glass scintillators with high density, high transparency and stable physical and chemical properties have gradually attracted people's attention. In addition, glass is low in cost and easy to mass produce. It is expected to replace scintillator crystals used in high-energy physics and other fields, and has broad application prospects.
[0003] With the rapid development of high-energy physics, the demand for scintillating materials is also increasing, so the research on scintillating materials also needs further development. The Chinese particle physics community proposed to build a circular electron-positron collider (CEPC). In order to achieve accurate measurements of the properties of Higgs, W and bosons, CEPC needs to cover a wide range of solid angles, excellent particle identification capabilities, accurate measurement of particle energy-momentum, high-precision collision vertex resolution, injection resolution and flavor marking. For the hadron calorimeter system of CEPC, suitable scintillating materials are needed. Scintillating glass has the advantages of simple preparation process, low cost and continuously adjustable composition, and is the priority target of hadron calorimeter. However, hadron calorimeter requires scintillating glass to have high density, considerable light yield, fast decay time and strong radiation resistance. In addition, the compact muon coil (CMS) of the large collider LHC at CERN, the European Organization for Nuclear Research, is also considering using scintillating glass to replace the original design. Moreover, the Large Electron-Ion Collider EIC in the United States is also considering developing scintillating glass calorimeter technology. It can be seen from this that scintillating glass is likely to be the most important scintillator in the next generation of high-energy physics experiments.
[0004] High density is an important indicator of scintillating materials in high-energy physics experiments. High-density scintillators have a shorter radiation length and better blocking ability for high-energy particles, which can improve the energy resolution of detectors and facilitate the compact design of large scientific equipment. The density of scintillating glass reported so far is unlikely to exceed 6g / cm 3, and high-density glass contains heavy metal oxides such as PbO, Bi2O3, and Lu2O3 without exception. For example, Chinese patent publication CN1087066A discloses a method for preparing scintillating glass with PbO and Bi2O3 as the main components. The scintillating glass contains a large amount of PbO, which seriously pollutes the environment. In addition, the light yield of this type of scintillating glass is very low and the luminous efficiency is poor, which limits its further practical application. Chinese patent CN110734223B discloses a lutetium-based silicate scintillating glass with a glass density of more than 6.5g / cm 3 , radiation resistance and mechanical strength, but Lu2O3 is expensive and has a radioactive background, making it difficult to use in large scientific facilities.
[0005] Activators in scintillation glass usually include rare earth luminescence centers, main group type luminescence centers, transition metal luminescence centers and nanocrystal quantum dots. The optical and scintillation properties of scintillation materials depend largely on the selection of luminescence centers and matrix. In the luminescence of discrete luminescence centers, the luminescence generated by the 5d-4f transition of the cerium ion luminescence center has a higher light output (spatial resolution) and a nanosecond decay time (temporal resolution). Therefore, the cerium ion luminescence center is currently the best activator in scintillation materials. In past reports, luminescence center ion-doped scintillation glass materials often only have one of the characteristics of high density / high light yield / fast decay. High density, high light yield and fast decay are themselves a contradictory unity, often showing that high-density glass has low light yield and low-density glass has high light yield. The main reasons are: first, the high-density glass matrix leads to a long absorption cutoff edge, which intensifies the self-absorption and charge migration effect of the luminescence center, resulting in low fluorescence intensity; second, scintillating glass with better performance requires a reducing atmosphere to ensure the low valence state of Ce ions, which increases the complexity of equipment and processes, and also causes some luminescence center ions to be oxidized due to high-temperature feeding / removal. Therefore, preparing the scintillating glass required for the CEPC hadron calorimeter is a very challenging problem.
[0006] Therefore, the art needs to develop a colorless transparent scintillating glass with high density, high light yield and fast decay time and a preparation method thereof. Summary of the invention
[0007] In order to solve the above problems, the purpose of the present invention is to prepare a colorless and transparent cerium-activated gadolinium aluminum borosilicate fluoride oxyscintillating glass, which has the performance advantages of high density and high light yield and can be used in nuclear radiation detection, high-energy physics experiments, X-ray medical imaging, neutron detection, national security monitoring and other fields.
[0008] The invention provides a cerium-doped gadolinium aluminum borosilicate fluoride oxygen scintillating glass, which comprises the following components: 16-61.5 mol% Gd2O3, 0-35 mol% GdF3, 1-10 mol% Al2O3, 15-40 mol% B2O3, 5-20 mol% SiO2 and 0.075-6.0 mol% luminescent center compound.
[0009] According to one embodiment of the present invention, the content of GdF3 in the scintillating glass is 0-35 mol%, and the content of the trivalent cerium compound is 0.125-6 mol%.
[0010] According to another embodiment of the present invention, Al2O3 in the scintillating glass is partially or completely replaced by one or more of AlF3, MgO, MgF2, CaO, CaF2, BaO, BaF, Ga2O3 and GaF3.
[0011] According to another embodiment of the present invention, the luminescent center compound is one or more of a trivalent cerium compound, a divalent europium compound, a divalent ytterbium compound, a trivalent terbium compound, a divalent tin compound, a trivalent antimony compound, and a divalent manganese compound; preferably, it is a trivalent cerium compound, and the trivalent cerium compound is one or more of CeF3, Ce2O3 or Ce(NO3)3.
[0012] According to another embodiment of the present invention, the scintillating glass further comprises a clarifier; preferably, the clarifier is Sb2O3.
[0013] The present invention also provides a method for preparing the cerium-doped gadolinium aluminum borosilicate fluoride-oxygen scintillating glass, comprising:
[0014] S1: uniformly mixing raw materials for forming the scintillation glass components in a molar ratio to obtain a first mixture, and melting the first mixture at a first predetermined temperature for a first predetermined time by a melting method to obtain a molten glass liquid;
[0015] And S2: pouring the molten glass into a mold preheated to a second predetermined temperature for casting, keeping the temperature at the second predetermined temperature for a second predetermined time for annealing, and cooling after annealing to obtain the cerium-doped gadolinium aluminum borosilicate fluoride-oxygen scintillating glass.
[0016] According to one embodiment of the present invention, the S1 step is carried out in a reducing atmosphere or in a vacuum; alternatively, the S1 step is carried out in an air atmosphere, and the raw material for forming SiO2 includes a reducing silicon source, and the reducing silicon source is one or more of Si3N4, SiC, SiO2 or silicon powder.
[0017] According to another embodiment of the present invention, the first temperature is 1100-1500° C., and the first predetermined time is 1.5-5.0 hours; the second temperature is 500-800° C., and the second predetermined time is 3.0-6.0 hours.
[0018] According to another embodiment of the present invention, in the S2 step, the annealing is performed at a variable temperature; preferably, after maintaining a constant temperature of 450-650°C for 2-4 hours, the temperature is reduced to 200°C at a cooling rate of 5-10°C / min, and then cooled to room temperature; or, after maintaining a constant temperature of 450-650°C at a rate of 30-60°C per hour for 2-4 hours, the temperature is reduced to 200°C at a cooling rate of 5-10°C / min, and then cooled to room temperature.
[0019] According to another embodiment of the present invention, the raw material for forming the trivalent cerium compound is one or more of CeO2, CeF3 or Ce(NO3)3.
[0020] According to another embodiment of the present invention, the raw material for forming B2O3 is one or more of H3BO3, BN, B4C and boron powder.
[0021] According to another embodiment of the present invention, the raw material for forming Al2O3 is one or more of Al2O3, AlN, Al(OH)3, AlF3 or aluminum powder.
[0022] The present invention also provides a gadolinium aluminum borosilicate fluorine oxygen scintillation glass for use in nuclear radiation detection, high energy physics experiments, X-ray medical imaging, neutron detection, and national security monitoring.
[0023] The present invention can reduce the melting temperature of glass and the degree of corrosion of the crucible by the glass solution by using gadolinium fluoride to partially replace gadolinium oxide, thereby increasing the density of the glass to 6.0g / cm 3 And above. Furthermore, the preparation process uses a reducing atmosphere for preparation or uses a reducing silicon source to replace or partially replace SiO2, which can effectively reduce the high-valent luminescent center ions and realize the preparation of colorless and transparent aluminum borosilicate scintillating glass in an air atmosphere. In addition, changing the activation concentration of cerium ions improves the scintillation and time performance of the glass. The light yield of the scintillating glass of the present invention exceeds 1000ph / MeV.
[0024] The colorless and transparent cerium-activated gadolinium aluminum borosilicate fluorine-oxygen scintillating glass prepared by the present invention has a simple preparation process and takes into account the performance advantages of high density and high light yield. Both the density and the scintillation performance meet the requirements of the CEPC hadron calorimeter and can be applied to nuclear radiation detection, high-energy physics experiments, X-ray medical imaging, neutron detection, and national security monitoring. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1Optical photographs of the scintillating glasses of Examples 1-8 are shown.
[0026] Figure 2 The X-ray absorption near edge structure (XANES) spectrum of Example 1 is shown.
[0027] Figure 3 Example 1 shows 137 Gamma spectrum under Cs radiation source.
[0028] Figure 4 The transmission spectra of Example 2 and Example 3 are shown.
[0029] Figure 5 Example 2 shows 137 Gamma spectrum under Cs radiation source.
[0030] Figure 6 Example 3 shows 137 Gamma spectrum under Cs radiation source.
[0031] Figure 7 It is shown that Example 2 and Example 3 are 137 Scintillation decay time curve under Cs radiation source.
[0032] Figure 8 Example 4 shows 137 Gamma spectrum under Cs radiation source.
[0033] Fig. 9 Example 4 shows 137 Scintillation decay time curve under Cs radiation source.
[0034] Fig.10 Example 5 shows 137 Gamma spectrum under Cs radiation source.
[0035] Fig.11 Example 5 shows 137 Scintillation decay time curve under Cs radiation source.
[0036] Fig.12 Example 6 shows 137 Gamma spectrum under Cs radiation source.
[0037] Fig.13 Example 6 shows 137 Scintillation decay time curve under Cs radiation source.
[0038] Fig.14 Example 7 shows 137 Gamma spectrum under Cs radiation source.
[0039] Fig.15 Example 7 shows 137Scintillation decay time curve under Cs radiation source.
[0040] Fig.16 Example 8 shows 137 Cs and 22 Gamma spectrum from a Na source.
[0041] Fig.17 Example 8 shows 137 Scintillation decay time curve under Cs radiation source. DETAILED DESCRIPTION
[0042] The present invention is described in detail below in conjunction with specific implementation modes.
[0043] The cerium-doped gadolinium aluminum borosilicate fluorine-oxygen scintillating glass of the present invention comprises 16-61.5 mol% Gd2O3, 0-35 mol% GdF3, 1-10 mol% Al2O3, 15-40 mol% B2O3, 5-20 mol% SiO2 and 0.125-6.0 mol% of a luminescent center compound. The total molar content of each component in the scintillating glass is 100%.
[0044] The present invention can reduce the melting temperature of glass and the erosion of crucible by glass solution by using gadolinium fluoride to partially replace gadolinium oxide, thereby increasing the density of glass to 6.0g / cm 3 And above, it is one of the highest values in borosilicate glass.
[0045] In an optional embodiment, Al2O3 in the scintillating glass may be partially or fully replaced by one or more of AF3, MgO, MgF2, CaO, CaF2, BaO, BaF, Ga2O3 and GaF3.
[0046] In an optional embodiment, the luminescent center compound can be a rare earth luminescent center such as a trivalent cerium compound, a divalent europium compound, or a trivalent terbium compound; the luminescent center compound can also be a medium transition metal luminescent center such as a divalent tin compound, a trivalent antimony compound, or a divalent manganese compound; or it can be one or more of the above luminescent centers. Preferably, it is a trivalent cerium compound, and the trivalent cerium compound is one or more of CeF3, Ce2O3, or Ce(NO3)3. The inventors of the present invention have found that the light yield and decay time of the scintillating glass can be adjusted by changing the doping amount of the luminescent center ion to meet the use requirements of the CEPC hadron calorimeter.
[0047] In an alternative embodiment, 0.125-6.0 mol % of a trivalent cerium compound is doped into the scintillating glass.
[0048] In an optional embodiment, the scintillation glass further includes a clarifier. Adding the clarifier can reduce bubbles in the glass and improve the performance of the glass. The clarifier can be Sb2O3 or the like.
[0049] The cerium-doped gadolinium aluminum borosilicate fluorine-oxygen scintillating glass can be prepared by the following preparation method. The preparation method comprises: S1: uniformly mixing raw materials for forming scintillating glass components in proportion to obtain a first mixture, and melting the first mixture by a melting method at a first predetermined temperature for a first predetermined time to obtain a molten glass liquid; and S2: pouring the molten glass liquid into a mold preheated to a second predetermined temperature for casting, keeping the temperature at the second predetermined temperature for a second predetermined time to perform annealing, and cooling after annealing to obtain the cerium-doped gadolinium aluminum borosilicate fluorine-oxygen scintillating glass.
[0050] Step S1 can be carried out in a reducing atmosphere or in a vacuum. The reducing atmosphere can be an Ar / H2 atmosphere or an N2 / H2 atmosphere. The reducing atmosphere can ensure that the Ce in the prepared glass is trivalent, thereby increasing the probability of radiation transition of the luminescent center in the glass and improving the scintillation performance of the glass. Alternatively, step S1 is carried out in an air atmosphere, and the SiO2 raw material for forming the glass includes a reducing silicon source, and the reducing silicon source is one or more of Si3N4, SiC, SiO or silicon powder. During the preparation process, the tetravalent cerium ions can be reduced to trivalent cerium ions by the reducing silicon source, so that the preparation of colorless and transparent cerium-doped gadolinium borosilicate scintillating glass can be achieved in an air atmosphere. The raw materials for forming SiO2 can be all reducing silicon sources, or part of them can be reducing silicon sources and the other part can be SiO2.
[0051] In step S1, the first temperature is 1100-1500°C, the first predetermined time is 1.0-5.0 hours, the second temperature is 500-800°C, the second predetermined time is 1.0-6.0 hours. Preferably, the first temperature is 1300-1500°C, and the first predetermined time is 2.0-5.0 hours.
[0052] In an optional embodiment, the raw material for forming the trivalent cerium compound is one or more of CeO2, CeF3 or Ce(NO3)3.
[0053] In an optional embodiment, the raw material for forming B2O3 is one or more of H3BO3, BN, B4C and B powder.
[0054] In an optional embodiment, the raw material for forming Al2O3 is one or more of Al2O3, AlN, Al(OH)3 or Al powder.
[0055] In step S2, the casting can be performed inside or outside the furnace, and high-performance scintillating glass can be obtained. Aluminum bronze plates, stainless steel plates and other materials can be used to fix the glass into shape. Removing the top and bottom layers of glass liquid during the casting process can ensure stable performance of the glass.
[0056] In an optional embodiment, variable temperature annealing can be used. Variable temperature annealing can reduce bubbles in the glass and improve transmittance and scintillation performance. The temperature change method can be, but is not limited to, maintaining a constant temperature of 450°C-650°C for 2-4 hours, then cooling to 200°C at a rate of 5-10°C / minute, and then cooling to room temperature; or, maintaining a constant temperature of 450-650°C at a rate of 30-60°C per hour for 2-4 hours, then cooling to 200°C at a rate of 5-10°C / minute, and then cooling to room temperature.
[0057] Preferably, the cerium-doped gadolinium aluminum borosilicate fluorine oxyscintillation glass of the present invention does not include radioactive elements, elements that may generate interference signals for high-energy detection, toxic elements, or colored elements. For example, Pm and Th elements are radioactive, La and Lu elements may generate interference signals for high-energy detection, W elements may produce coloring during glass preparation, Pb and Tl elements may be toxic during the preparation process, and may discolor the glass under the influence of radiation, and Tb and Eu elements have too long a scintillation decay time, and are not suitable to appear in the scintillation glass components. If cost is taken into consideration, elements with too high cost, such as Lu, Ge, etc., may not be included.
[0058] The cerium-doped gadolinium aluminum borosilicate fluorine-oxygen scintillating glass of the present invention is used for detecting high-energy particles and is applied in nuclear radiation detection, high-energy physics experiments, X-ray medical imaging, neutron detection, and national security monitoring.
[0059] The present invention will be described in detail below with reference to the examples. Unless otherwise specified, the raw materials and equipment used in the examples can be purchased through commercial channels and operated under the guidance of the instructions.
[0060] The numerical unit before each component in the glass in the following embodiments is mol%. For example, "35Gd2O3" means that the content of Gd2O3 in the glass is 35mol%, and the contents of other components can be deduced by analogy.
[0061] Example 1: Colorless and transparent cerium-doped gadolinium borosilicate scintillating glass 35Gd2O3-23.5GdF3-1Al2O3-22B2O3-18SiO2-0.5CeF3
[0062] High-purity (99.99%) gadolinium oxide (Gd2O3), gadolinium fluoride (GdF3), aluminum oxide (Al2O3), silicon dioxide (SiO2), silicon carbide (SiC), boric acid (H3BO3), and cerium fluoride (CeF3) are taken as raw materials in a stoichiometric ratio, mixed evenly, and prepared into a mixture.
[0063] The mixture was transferred into a covered corundum crucible and melted in an air atmosphere at a melting temperature of 1300°C for 2.5 hours. The molten liquid was poured onto a steel plate preheated to 600°C for quenching to form glass.
[0064] The prepared glass was annealed in a muffle furnace heated to 600°C. After keeping the temperature for 3.0 hours, the temperature was lowered to 200°C at a rate of 10°C / min, and then cooled to room temperature in the furnace.
[0065] The colorless and transparent cerium-doped gadolinium borosilicate scintillating glass is obtained by cutting, surface grinding and polishing the annealed scintillating glass primary product.
[0066] Example 2: Colorless and transparent cerium-doped gadolinium borosilicate scintillating glass 35Gd2O3-23GdF3-1Al2O3-22B2O3-18SiO2-1CeF3
[0067] High-purity (99.99%) gadolinium oxide (Gd2O3), gadolinium fluoride (GdF3), aluminum oxide (Al2O3), silicon dioxide (SiO2), silicon nitride (Si3N4), boric acid (H3BO3), and cerium fluoride (CeF3) are weighed by mole as raw materials, mixed evenly, and prepared into a mixed material.
[0068] The mixed raw materials are transferred into a covered corundum crucible and melted in an air atmosphere at a melting temperature of 1360°C for 3.0 hours. The molten liquid is poured onto a steel plate preheated to 600°C for quenching to form glass.
[0069] The prepared glass was annealed in a muffle furnace heated to 610°C. After keeping the temperature for 3.0 hours, the temperature was lowered to 200°C at a rate of 10°C / min, and then cooled to room temperature in the furnace.
[0070] The colorless and transparent cerium-doped gadolinium borosilicate scintillating glass is obtained by cutting, surface grinding and polishing the annealed scintillating glass primary product.
[0071] Example 3: Colorless and transparent cerium-doped gadolinium borosilicate scintillating glass 35Gd2O3-22GdF3-1Al2O3-22B2O3-18SiO2-2CeF3
[0072] High-purity (99.99%) gadolinium oxide (Gd2O3), gadolinium fluoride (GdF3), aluminum oxide (Al2O3), silicon dioxide (SiO2), silicon nitride (Si3N4), boric acid (H3BO3), and cerium fluoride (CeF3) are weighed as raw materials in a molar ratio, and the other steps are the same as those in Example 2.
[0073] Example 4: Colorless and transparent cerium-doped gadolinium borosilicate scintillating glass 28Gd2O3-30GdF3-3Ga2O3-18.5B2O3-18.5SiO2-2CeF3
[0074] High-purity (99.99%) gadolinium oxide (Gd2O3), gadolinium fluoride (GdF3), gallium oxide (Ga2O3), silicon dioxide (SiO2), silicon nitride (Si3N4), boric acid (H3BO3), and cerium fluoride (CeF3) are weighed as raw materials in a molar ratio, mixed evenly, and prepared into a mixture. The mixed raw materials are transferred to a covered corundum crucible and melted in an air atmosphere at a melting temperature of 1435°C and a holding time of 6.0 hours. The molten liquid is poured onto a steel plate preheated to 650°C for quenching to form glass.
[0075] The prepared glass was annealed in a muffle furnace heated to 650°C, with the temperature lowered by 50°C every hour. After keeping the temperature for 6.0 hours, the temperature was lowered to 200°C at a rate of 10°C / min, and then cooled to room temperature in the furnace.
[0076] The remaining steps are the same as in Example 2.
[0077] Example 5: Colorless and transparent cerium-doped gadolinium borosilicate scintillating glass 20Gd2O3-33GdF3-15MgF2-20B2O3-5BN-5SiO2-1CeO2
[0078] High-purity (99.99%) gadolinium oxide (Gd2O3), gadolinium fluoride (GdF3), magnesium fluoride (MgF2), silicon dioxide (SiO2), boric acid (H3BO3), boron nitride (BN), and cerium dioxide (CeO2) are weighed as raw materials in a molar ratio, mixed evenly, and prepared into a mixture.
[0079] The mixed raw materials were transferred into a covered corundum crucible and melted in an air atmosphere at a melting temperature of 1350°C for 4.0 hours. The molten liquid was poured onto a steel plate preheated to 500°C for quenching to form glass.
[0080] The prepared glass was annealed in a muffle furnace heated to 500°C. After keeping the temperature for 2.0 hours, the temperature was lowered to 200°C at a rate of 10°C / min, and then cooled to room temperature in the furnace.
[0081] The remaining steps are the same as in Example 2.
[0082] Example 6: Colorless and transparent cerium-doped gadolinium borosilicate scintillating glass 35Gd2O3-23.875GdF3-1Al2O3-22B2O3-18SiO2-0.125CeF3
[0083] The implementation steps are the same as in Example 1.
[0084] Example 7: Colorless and transparent cerium-doped gadolinium borosilicate scintillating glass 32Gd2O3-33GdF3-3AlF3-25B2O3-5SiO2-6CeF3
[0085] The implementation steps are the same as in Example 5.
[0086] Example 8: Colorless and transparent praseodymium-doped gadolinium borosilicate scintillating glass 36Gd2O3-32GdF3-3AlF3-24B2O3-5SiO2-1PrF3
[0087] High-purity (99.99%) gadolinium oxide (Gd2O3), gadolinium fluoride (GdF3), aluminum fluoride (AlF3), silicon dioxide (SiO2), silicon nitride (Si3N4), boric acid (H3BO3), and praseodymium fluoride (PrF3) are weighed as raw materials in a molar ratio of , mixed evenly, and prepared into a mixture.
[0088] The implementation steps are the same as in Example 5.
[0089] The scintillating glasses prepared in comparative examples 1-8 were characterized. Optical photographs of the colorless and transparent cerium-doped gadolinium borosilicate scintillating glasses prepared in examples 1-5 were taken by a digital camera. The X-ray absorption near-edge structure (XANES) spectrum of Ce ions was measured on the 1W2B beamline of the Beijing Synchrotron Radiation Facility (BSRF, Beijing, China). A silicon photomultiplier tube (MPC Hamamatsu, S13360-6050CS, with an effective photosensitive area of 6×6 mm 2 ) Get the flashing glass in 137 Energy spectrum under Csγ-ray excitation. The light yield and energy resolution of the scintillating glass are further obtained from the energy spectrum. A photomultiplier tube (PMTXP2020, Photonis) is used to obtain the light yield and energy resolution of the scintillating glass under Csγ-ray excitation. 137 The waveform signal under Csγ-ray excitation is used to obtain the scintillation decay time of the glass by averaging the waveform.
[0090] The digital photos of Embodiments 1 to 8 are as follows: Figure 1 shown. Figure 1The middle picture shows optical photographs of scintillating glasses according to Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Example 7 and Example 8 from left to right. As shown in the figure, there are almost no bubbles in the glass, and a small amount of insoluble gadolinium exists on the surface of the glass. In addition, the density of the scintillating glasses prepared in all the examples reaches 6.0 g / cm 3 .
[0091] The X-ray absorption near edge structure (XANES) spectrum of Ce ions in Example 1 is as follows: Figure 2 As shown in the figure, the standard samples of trivalent and tetravalent Ce compounds (Ce(NO3)3 and CeO2) are included. The energy of 5726eV corresponds to Ce 3+ 5d→4f transition, while Ce 4+ The oxidation state of Ce has two peaks, located at 5734eV and 5742eV, respectively, which are 2p→5d transitions. The XANES spectrum of Example 1 only has Ce 3+ ion characteristics, which indicates that Ce in the glass 4+ All restored to Ce 3+ Therefore, Example 1 exhibits effective scintillation luminescence.
[0092] Example 1 137 The energy spectrum under Csγ-ray excitation is as follows Figure 3 As shown. The light yield of Example 1 under gamma rays is 1076 ph / MeV, and the energy resolution is 49.6%@662 keV. The light yield of the glass reaches 1000 ph / MeV and above, and it can be observed that the glass has an obvious full energy peak at 662 keV.
[0093] The transmission spectra of Example 2 and Example 3 are as follows: Figure 4 As shown. Under the same glass matrix composition, as Ce 3+ As the concentration increases, the absorption edge of the glass red shifts. 3+ The quenching effect and self-absorption gradually increase, which may lead to the degradation of the scintillation performance of the glass.
[0094] Example 2 137 The energy spectrum under Csγ-ray excitation is as follows Figure 5 As shown. Figure 5 The backscattering peak at about 180 keV can be clearly seen in the figure. 137 The gamma rays from the Cs source and the Compton backscattered photons produced by the hard matter around the scintillating glass return to the signal produced by the scintillating glass. At the same time, it can be clearly seen from the figure that 137The full energy peak of Cs662keV indicates that the glass prepared in this embodiment has good scintillation performance. Through Gaussian fitting and calculation, the light yield of Example 2 under gamma rays is 1146ph / MeV, and the energy resolution is 25.1%@662keV.
[0095] Example 3 137 The energy spectrum under Csγ-ray excitation is as follows Figure 6 As shown. The light yield of Example 3 under gamma rays is 1070ph / MeV, and the energy resolution is 24.0%@662keV. Due to the concentration quenching effect, the light yield of Example 2 is higher than that of Example 3. However, its energy resolution is getting better and better. During charge integration, the dark noise cases from SiPM are reduced, and the statistical error is reduced, so the energy resolution of the scintillating glass becomes better.
[0096] The scintillation decay time curves of Example 2 and Example 3 are as follows: Figure 7 As shown. Example 2 and Example 3 137 The decay time curve under Cs radiation source can be found in Figure 7 Through exponential fitting, the scintillation decay times of Example 2 and Example 3 are 119ns (accounting for 5.0%), 894ns and 92ns (accounting for 8.0%), 473ns respectively. The scintillation glasses of the two examples show two components, fast and slow. The former is attributed to the direct capture of electron-hole pairs in the glass by cerium ions, and the latter is from Gd 3+ →Ce 3+ The energy transfer process. 3+ As the concentration increases, the interaction between Ce and Ce increases, the probability of energy transfer between central excited states increases, and excited electrons are prone to concentration quenching. Therefore, the decay time of the glass is shortened.
[0097] Example 4 137 The energy spectrum under Csγ-ray excitation is as follows Figure 8 As shown. The light yield of Example 4 under gamma rays is 1019ph / MeV, and the energy resolution is 27.4%@662keV. By changing the glass heat treatment process, the glass still maintains extremely high optical quality, and the internal bubbles are significantly reduced. The light yield of Example 4 is still above 1000ph / MeV.
[0098] Example 4 137 The decay time curve under Cs radiation source can be found in Fig. 9 After fitting calculation, its decay time is 103.8 (4.4%), 764.8ns. Due to the change of heat treatment process, the defects in the glass increase slightly, and the probability of defects capturing electron-hole pairs increases. Therefore, the slow component in the glass decay time increases.
[0099] Example 5 137 The energy spectrum under Csγ-ray excitation is as follows Fig.10 The light yield of Example 5 under gamma rays is 884 ph / MeV, and the energy resolution is 31.2%@662 keV. Using MgF2 as a network intermediate to replace Al2O3 in the glass increases the optical alkalinity of the glass, which makes Ce in the glass 3+ The self-absorption effect is aggravated, which eventually leads to a decrease in the scintillation performance of Example 5, and the light yield is around 900ph / MeV.
[0100] Example 5 137 The decay time curve under Cs radiation source is as follows Fig.11 As shown, their decay times are 80.8 (4.9%) and 1251.2 ns respectively. The ionic radius / molar volume of the alkaline earth metal oxide will affect the decay time of the glass. The larger the ionic radius, the longer the decay time of the glass. Therefore, the decay time of Example 5 is longer, and the slow component exceeds 1000 ns.
[0101] Example 6 137 The energy spectrum under Csγ-ray excitation is as follows Fig.12 The light yield of Example 6 under gamma rays is 1044 ph / MeV, and the energy resolution is 26.8%@662 keV. This proves that low concentration Ce 3+ Doped scintillating glasses also have higher light yields.
[0102] Example 6 137 The decay time curve under Cs radiation source is as follows Fig.13 As shown in Figure 2, its decay time is 1091.0ns. 3+ Doped, the scintillation decay time of the glass is longer.
[0103] Example 7 137 The energy spectrum under Csγ-ray excitation is as follows Fig.14 The light yield of Example 7 under gamma rays is 696 ph / MeV, and the energy resolution is 41.8%@662 keV. High concentration Ce 3+ For doped scintillating glass, due to concentration quenching, the light yield of the glass decreases to around 700ph / MeV.
[0104] Example 7 137 The decay time curve under Cs radiation source is as follows Fig.15 As shown in Figure 1, its decay time is 287.0ns. Due to the concentration quenching of excited electrons, the scintillation decay time of glass is very short, less than 300ns.
[0105] Example 8 137 Cs and 22The energy spectrum under Naγ-ray excitation is as follows Fig.16 As shown. The light yield of Example 8 under gamma rays is 610 ph / MeV, and the energy resolution is 42.9%@662keV. Example 8 proves that Pr 3+ Doped gadolinium borosilicate glass also has good scintillation properties.
[0106] Example 8 137 The decay time curve under Cs radiation source is as follows Fig.17 As shown in Figure 2, their decay times are 147.6 (60.9%) and 1486.1 ns respectively. The former is attributed to the direct capture of electron-hole pairs in the glass by praseodymium ions, and the latter is from Gd 3+ →Pr 3 + energy transfer process.
[0107] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A gadolinium aluminum borosilicate fluoride oxyscintillating glass, characterized in that: The scintillation glass comprises the following components: 16-61.5 mol% Gd2O3, 0-35 mol% GdF3, 1-10 mol% Al2O3, 15-40 mol% B2O3, 5-20 mol% SiO2 and 0.125-6.0 mol% of the luminescent center compound.
2. The gadolinium aluminum borosilicate oxyfluoride scintillating glass according to claim 1, characterized in that: The content of GdF3 in the scintillating glass is 0 to 35 mol%.
3. The gadolinium aluminum borosilicate oxyfluoride scintillating glass according to claim 1, characterized in that: The Al2O3 in the scintillating glass is partially or completely replaced by one or more of AlF3, MgO, MgF2, CaO, CaF2, BaO, BaF2, Ga2O3, and GaF3.
4. The gadolinium aluminum borosilicate oxyfluoride scintillating glass according to claim 1, characterized in that: The luminescent center compound is one or more of a trivalent cerium compound, a divalent europium compound, a trivalent terbium compound, a divalent tin compound, a trivalent antimony compound, and a divalent manganese compound; preferably, it is a trivalent cerium compound, and the trivalent cerium compound is one or more of CeO2, CeF3 and Ce2O3.
5. The gadolinium aluminum borosilicate oxyfluoride scintillating glass according to claim 1, characterized in that: The scintillating glass further comprises a clarifier, such as antimony oxide and sodium nitrate; preferably, the clarifier is antimony oxide.
6. A method for preparing the gadolinium aluminum borosilicate fluoride oxyscintillating glass according to any one of claims 1 to 5, characterized in that: include: S1: uniformly mixing raw materials for forming the scintillation glass components in a molar ratio to obtain a first mixture, and melting the first mixture at a first predetermined temperature for a first predetermined time by a melting method to obtain a molten glass liquid; and S2: pouring the molten glass into a mold preheated to a second predetermined temperature for casting, and maintaining the temperature at the second predetermined temperature for a second predetermined time for annealing to obtain the gadolinium aluminum borosilicate fluoride oxygen scintillation glass.
7. The preparation method according to claim 6, characterized in that: The S1 step is performed in a reducing atmosphere or in a vacuum; alternatively, the S1 step is performed in an air atmosphere, and the raw material for forming SiO2 includes a reducing silicon source, and the reducing silicon source is one or more of Si3N4, SiC, SiO or silicon powder.
8. The preparation method according to claim 6, characterized in that: The first temperature is 1100-1500° C., and the first predetermined time is 1.0-5.0 hours; the second temperature is 500-800° C., and the second predetermined time is 1.0-6.0 hours.
9. The preparation method according to claim 6, characterized in that: In the step S2, the annealing is performed at a variable temperature; preferably, the temperature is kept constant at 450-650°C for 2-4 hours, then the temperature is reduced to 200°C at a cooling rate of 5-10°C / min, and then cooled to room temperature; or, the temperature is kept constant at 450-650°C for 2-4 hours, then the temperature is reduced to 200°C at a cooling rate of 5-10°C / min, and then cooled to room temperature.
10. The preparation method according to claim 6, characterized in that: The raw materials for forming B2O3 are one or more of H3BO3, BN, B4C and B powder.
11. The preparation method according to claim 6, characterized in that: The raw materials for forming Al2O3 are one or more of Al2O3, AlN, Al(OH)3, AlF3 or Al powder.
12. The gadolinium aluminum borosilicate fluoride oxygen scintillating glass according to any one of claims 1 to 5 is used for detecting high-energy particles, and is used in nuclear radiation detection, high-energy physics experiments, X-ray medical imaging, neutron detection, and national security monitoring.
Citation Information
Patent Citations
Novel borosilicate scintillation glass
CN102390929A
Transparent glass scintillators, methods of making same and devices using same
CN103597374A
Gadolinium borosilicate scintillating glass and preparation method thereof
CN103693847A
Colorless transparent cerium-activated borosilicate scintillation glass and preparation method thereof
CN108249757A
Scintillation glass of terbium ion doped gadolinium borosilicate and preparation method of scintillation glass
CN112851117A